Coumarin: An emerging antiviral agent. Issue 1 (January 2020) - Mishra, Shruti; Pandey, Achyut; Manvati, Siddharth
Abstract: Viral infections are responsible for many illnesses, and recent outbreaks have raised public health concerns. Despite the availability of many antiviral drugs, they are often unsuccessful due to the generation of viral mutants and less effective against their target virus. Identifying novel antiviral drugs is therefore of critical importance and natural products are an excellent source for such discoveries. Coumarin is one such natural compound that is a potential drug candidate owing to its properties of stability, solubility, and low toxicity. There are numerous evidences showing its inhibitory role against infection of various viruses such as HIV, Influenza, Enterovirus 71 (EV71) and coxsackievirus A16 (CVA16). The mechanisms involve either inhibition of proteins essential for viral entry, replication and infection or regulation of cellular pathways such as Akt-Mtor (mammalian target of rapamycin), NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells), and anti-oxidative pathway including NrF-2 (The nuclear factor erythroid 2 (NFE2)-related factor 2). This review summarizes the present state of understanding with a focus on coumarin's antiviral effect and their possible molecular mechanisms against Influenza virus, HIV, Hepatitis virus, Dengue virus and Chikungunya virus. Abstract : Microbiology; Pharmaceutical science; Health sciences; Public health; Pharmacology; Coumarin; Antiviral; Viral replication; Natural product; Inhibitor; Mechanism.